Authorithy of Preliminary Evidence Audit in Indonesia: Administrative Policy or Criminal Policy? - Anis Wahyu Hermawan; Yudha Pramana; Leo B. Barus (Scientia Integritas Utama, 2022)
There are still pros and cons regarding the position of preliminary evidence audit in the field of taxation in Indonesia, whether the authority is part of criminal policy or administrative policy. It is concluded that KUP Law, PP No. 50/2022, and PMK-177/PMK.03/2022 have never granted authority as part of criminal laws and policies even though the implementation was carried out by Civil Servant Investigators (PPNS) within the Directorate General of Taxes (DGT). This is based on a systematic interpretation of the definition of preliminary evidence examination as referred to in Article 1 point 27 and number 26 of the KUP Law and Article 43A of the KUP Law with Article 59 paragraph (7) of the Government Regulation Number 50 of 2022.